Editorial Board IJBB Vol. 9 No. 1 September 2021 - Putu Perdana Kusuma Wiguna (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2021)
Editorial Board IJBB Vol. 9 No. 1 September 2021